From Mandatory School Gymnastics to Physical Training for Youth. How the Société Fédérale de Gymnastique Became a “Gymnastic State” Dedicated to the Physical Preparation of Swiss Youth From 1873 to 1907 - Mayencourt, Gil (Front Sports Act Living, 2021)
The aim of this contribution is to analyse the special role that gymnastics clubs played, under the umbrella of the Société Fédérale de Gymnastique (SFG), in the formation of the Swiss nation and in the representation of a strong and united national youth at a time when the unity represented by the Swiss federal State founded in 1848 was strongly questioned by the conservative opposition. The purpose is mainly based on extensive statistical data gathered within the SFG about its members throughout the country at three particular moments (1873, 1895, and 1907) and on institutional archival funds. Our analysis is based on three successive points: after defining the relationship between the SFG and the Swiss Federal State (founded in 1848) for the unification and defense of the homeland, whether in terms of institutional mimicry or the building of a “national youth,” a second part defines which type of “youth” is specifically targeted by the SFG and what it meant at the time to be a “young” or an “old” gymnast, in particular through the participation of the SFG in the National exhibition of Geneva in 1896. Finally, a last part widens the perspective by highlighting, on one side, the cultural, political, and cantonal constraints on national expansion through youth of Swiss gymnastics and, on the other side, how these constraints have generated unifying and patriotic ambitions and discourses within the SFG.